Rare genetic variants affecting urine metabolite levels link population variation to inborn errors of metabolism - Yurong Cheng (Nature Portfolio, 2021)
Metabolites are indicators of health and disease; genetic studies can reveal variants influencing their levels. Here, the authors investigate the contribution of rare, exonic variants on the levels of urine metabolites and generate predictions on metabolic consequences underlying metabolic disease.